Rate and extent of top spoilage losses of alfalfa silage stored in horizontal silos1 - Dickerson, J.T.; Niwa, Y.; Bolsen, K.K.; Brent, B.E.; Lin, C.; Bradford, J.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Effects of covering, time, and depth from the surface on the rate and extent of top spoilage losses in alfalfa silages stored in horizontal silos were studied under pilot- and farm-scale conditions. Covering silages increased silage DM and nutrient recoveries, regardless of time or depth from the original surface, when compared to uncovered counterparts. Treatment × location × time interactions (P<.001) were observed for pH, lactic acid, and DM recovery in uncovered silages. By week 2 post-ensiling, significant deterioration had occurred in the top foot of uncovered silages, as evidenced by higher pH (7.36) and lower lactic acid (2.1% of the silage DM) and DM recoveries (85.6% of the DM ensiled). After week 4 post-ensiling, significant deterioration had occurred in the second foot from the surface, and it continued into the third foot after week 7. These data indicate that protecting the silage stored in the top 3 ft of horizontal silos immediately after filling should greatly increase storage efficiency.
Keywords: Beef; Silage; Alfalfa; Top spoliage; Horizontal silos